2011
DOI: 10.1371/journal.pone.0017209
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Sintering of Silver Nanoparticle Ink Studied by In-Situ TEM Probing

Abstract: Metallic nanoparticle inks are used for printed electronics, but to reach acceptable conductivity the structures need to be sintered, usually using a furnace. Recently, sintering by direct resistive heating has been demonstrated. For a microscopic understanding of this Joule heating sintering method, we studied the entire process in real time inside a transmission electron microscope equipped with a movable electrical probe. We found an onset of Joule heating induced sintering and coalescence of nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(44 citation statements)
references
References 48 publications
1
43
0
Order By: Relevance
“…115 This process occurs on a timescale of a few milliseconds to seconds and is called rapid electrical sintering (RES). As a consequence, electrical sintering is basically a local heating of the printed material while keeping the thermal stress to the substrate material to a minimum.…”
Section: Electrical Sinteringmentioning
confidence: 99%
“…115 This process occurs on a timescale of a few milliseconds to seconds and is called rapid electrical sintering (RES). As a consequence, electrical sintering is basically a local heating of the printed material while keeping the thermal stress to the substrate material to a minimum.…”
Section: Electrical Sinteringmentioning
confidence: 99%
“…Not only chemical binders, natural binders can also be used which are environmental friendly. Few other sintering techniques proved significance in silver inks are photonic sintering [106] , plasma sintering [116,117] , laser sintering, microwave sintering [114,115] and electric sintering [118,119] . Recently, silver inks have progressed successfully in developing low temperature [71,112] sintering and room temperature sintering [103,113] .…”
Section: Complex Composition Of Nanoparticles and Chemicalsmentioning
confidence: 99%
“…[30][31][32][33][34] Other in situ TEM techniques allow the investigation of consolidation mechanisms by exposing particle agglomerates to electrical currents. 35,36 The early stage sintering of platinum (Pt) due to thermal annealing during in situ scanning transmission electron microscopy (STEM) has been reported in the literature. Asoro et al have measured dihedral angles between individual particles supported on amorphous carbon as a function of temperature 30 whereas Simonsen et al 31 observed thermally activated Ostwald ripening of Pt catalyst particles on SiO 2 substrates.…”
Section: Introductionmentioning
confidence: 99%